Effects of cinnamon and rosemary oils on egg production, egg quality,hatchability traits and blood serum mineral contents in laying quails (Coturnix coturnix Japonica) - Şimşek, Ülkü Gülcihan; Ciftci, Mehmet; Özçelik, Mehtap; Azman, Mehmet Ali; Tonbak, Fadime; Özhan, Nejla (My University, 2015)
This study was carried out to evaluate the effects of cinnamon (CO), rosemary (RO) and a mixture (MO) of theseplants oil on egg production, feed intake, feed conversion rate, external and internal egg quality, blood serum mineral conte nts andhatchability traits in different sex ratios of [1/3 and 1/5, (?/?)] in laying quails. A total of 192 quail were distributed into specialcages (12 quails/per cage) including three experimental diets and control. The experiment was continued two months. At the en d ofthe study, 12 birds from each group were slaughtered in order to collect blood samples. The levels of Cu, Co, Cr, Zn, Fe, K, Na andMg in serum were determined. The highest egg weight was found in RO group, while it was lowest in MO group (P<0.05). Additionof diatery CO improved hen -day egg production as well as feed conversion rate (P<0.05). Feed intake was found to be similar amongthe groups (P>0.05). While egg shell rate increased in CO group (P<0.05), the ratios of egg yolk, egg albumen and shape index didnot differ among the treatments (P>0.05). Although the effect of diets implemented in the experimental groups on the fertility wasfound to be significant (P<0.05) this effect on the hatchability traits in both sex ratios was not significant (P>0.05). While the serumK level was significantly higher in CO group (P<0.05) the level of Zn in group CO (P =0.078) and the level of Co in group RO werefound slightly higher (P=0.086). The other findings of mineral contents were similar among the groups (P>0.05). Consequence o fthis study showed that CO had a positive effects on egg production and egg shell qua lity. Mixture of CO and RO had negative effectson egg weight and cumulative egg weight.
Keywords: Veterinerlik